iPad and iPad Pro For Dummies, 11th Edition - Baig, Edward; LeVitus, Bob; Chaffin, Bryan (--For dummies., 2020)
The A to Z guide to getting the most from your iPad Your iPad is a magical piece of technology connecting you to the rest of the world pretty much anytime and anywhere. Super thin and (well, almost) light as a feather, it allows you to keep up with your day to day duties, stay in touch with family and friends, catch up with work, relax with books and movies, or even create your own works of art! Given all it's capable of, it's essential to have a guide to help you make the most of your device. The latest edition of iPad and iPad Pro for Dummies helps users of all experience levels navigate this amazing looking glass. Assuming no prior knowledge, it takes you from the basics-including getting to know the iPad and adding useful accessories such as keyboards and pencils-to setting up email, connecting with other devices, maintaining files, and researching and installing the best apps for you. Discover the simple steps to get up and running Make your iPad work better and faster for you Explore the features of the brand new iPadOS Get easy fixes to common problems Pick up your copy today and find out just how sweet life in Apple tablet form can be!